Corticosteroids in the management of the paediatric epilepsies. Issue 4 (21st March 2005) - Gupta, R; Appleton, R
Abstract : Corticosteroids (predominantly prednisolone and hydrocortisone) and adrenocorticotropic hormone (ACTH) have been used in the treatment of the epilepsies for over 50 years. 1, 2 Over the past 30 years most reports have focused on epilepsy syndromes and epileptic encephalopathies resistant to treatment with the more conventional anticonvulsant and antiepileptic drugs (AEDs) and specifically West syndrome. There has been relatively little attention on the role of corticosteroids in treating other epilepsies.